Bronze Age pottery from the River Ljubljanica - Murgelj, Ida (Arheološki vestnik, 2025)
The article discusses a selection of Bronze Age pottery finds from the River Ljubljanica, in central Slovenia. The pottery comes from different locations, namely the wider area of Verd, Japljeve ujske, Zaloke-Črni potok, Nove gmajne, Lipavec, Bistra, Dolnji Breg, Tri Lesnice and the wider area of Blatna Brezovica, while some finds lack precise location data as a significant portion was collected unsystematically. It was recovered during different diving campaigns by both professional archaeologist divers and amateur divers, and is kept in the National Museum of Slovenia. It dates from the Early to the Late Bronze Age (BA A2–Ha A), but predominantly to the Oloris-Podsmreka horizon spanning the late part of the Middle and the early part of the Late Bronze Age (BA B2/C–BA D/Ha A1).